Selected Heavy Metals Levels (Cu, Cr, Cd, Pb, Fe) in Gwadabawa Lake, Sokoto State, Nigeria - Aminu Umar Imam; Yusuf Sarkingobir; Ummu Tukur (International Journal of Minerals, 2024)
The main aim of this work was to determine the concentrations of some heavy metals, specifically Cu, Cd, Pb, Cr and Fe in Gwadabawa lake, Gwadabawa Local Government, Sokoto State using standard methods (atomic absorption spectroscopy) and materials of analytical grade. The results were analyzed. The range of Fe concentration was 0.01 ± 0.001 to 1.37 ± 0.3(ppm), and range of Cu concentration determined was 0.00 to 0.02±0.008(ppm). The range of Cr was 0.02± 0.007 to 6.00± 0.32(ppm), the range of Cd was 0.03±0.10 to 1.68±0.3, and the range of Pb was 0.01± 0.001 to 0.02± 0.04(ppm). Cu CDI calculated in adults and children shows values higher than 1 in water collected from point B, and point A. This implies that consumption at these concentrations is likely to pose risk to adults and children. Likewise, only water in point A and B shows Pb value of more than 1, therewith, possibility of instigating risk due to consumption in children is likely. One point shows a HI of more than 1 (5.7/3805). Likewise, the water at point A and B shows HI at more than 1 (1.1/03451 and 6.96280084 respectively). Effective measures should be put in place to avoid lake water pollution to safeguard users.
Keywords: Environmental pollution; Heavy metals; Lead; lake; water